Rediscovery and an additional record of Terminalia kangeanensis (Combretaceae), a long lost threatened species from Indonesia - Metusala, Destario; Al Farishy, Dee Dee (Phytotaxa, 2022)
Terminalia kangeanensis (Combretaceae) is an endemic and threatened species (IUCN Redlist - Vulnerable) known only from several small islands of Kangean archipelago, Indonesia. The latest collections were made in 1919 and the first description was formally published in 1924. Since then, there was no additional information that indicates their existence. This paper has reported the rediscovery and a new record for its natural distribution for more than 100 years since its last known collections. This paper provides additional description, ecological information, insight on its conservation challenges, and also the first photos of living T. kangeanensis ever published.